2017
DOI: 10.1088/1755-1315/80/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of noise pollution level in a University campus in South India

Abstract: Abstract. Noise comprises those sounds occurring around us that are not part of the environment under consideration. Noise is also a type of pollution and impacts on our health and wellness. The prevalence of noise is increasing in magnitude and severity because of growing population and urbanization. Noise pollution leads to many chronic and socially significant impacts. This study analyzes the level of noise at different points in SRM University. As the University encompasses a hospital also, it is more impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
1
17
1
Order By: Relevance
“…According to analyses carried out during the soundwalk interviews in the park, users perceived the park's area as the least friendly, loud, and annoying in parts which usually border the main road. Similar results were obtained in academic campuses in Turkey [82], India [83], or Brazil [87].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…According to analyses carried out during the soundwalk interviews in the park, users perceived the park's area as the least friendly, loud, and annoying in parts which usually border the main road. Similar results were obtained in academic campuses in Turkey [82], India [83], or Brazil [87].…”
Section: Discussionsupporting
confidence: 83%
“…In addition to acoustic valor of greenery in university campuses that is marked in our research, it should be considered as one element in a more complex environmental system, where soundscape together with water management [ 73 ], energy consumption [ 74 ], or climate mitigation actions [ 75 ] can create academic campuses as sustainable educations hubs influencing the surrounding and promoting a built environment of 21st century. Such actions in redesigning academic campuses according to modern urbanization concepts can be observed in many countries around the globe like France [ 76 ], Spain [ 77 ], Italy [ 78 ], Poland [ 79 ], Germany [ 70 ], Finland [ 80 ], US [ 81 ], Turkey [ 82 ], India [ 83 ], China [ 84 ], Singapore [ 85 ], Malaysia [ 86 ], or Brazil [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The noise data is measured in two daytime sessions; one in the morning (9AM-12PM) and another one in the noon session (2PM-5PM) for two semesters of study period [22]. Each semester runs from November to December 2018 and from February to March 2019 [23]. The sound level meter is used as the noise level measuring tool at three measurement points of M1, M2 and M3 as shown in Fig.…”
Section: Methodology 21 Measurement Of Equivalent Continuous Noise Level Corresponding To Time Zonementioning
confidence: 99%
“…It is observed that indoor acoustic quality is a critical indicator for architects and engineers during the design and renovation of structures [2]. Indoor acoustic quality enables us to evaluate a building's energy efficiency by analyzing its energy usage in relation to the indoor environment quality that can be achieved indoors [3]. Educational areas are those in which much time is spent reading, writing, examining maps, or focusing attention on monitors.…”
Section: Introductionmentioning
confidence: 99%